2002
DOI: 10.1128/jcm.40.9.3350-3357.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Noninvasive Method for Molecular Detection and Differentiation of Malassezia Yeast Species on Human Skin and Application of the Method to Dandruff Microbiology

Abstract: Malassezia fungi have been the suspected cause of dandruff for more than a century. Previously referred to as Pityrosporum ovale, Pityrosporum orbiculare, or Malassezia, these fungi are now known to consist of at least seven Malassezia species. Each species has a specific ecological niche, as well as specific biochemical and genetic characteristics. Malassezia yeasts have fastidious culture conditions and exceedingly different growth rates. Therefore, the results of surveys of Malassezia based on culture metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 47 publications
1
148
1
6
Order By: Relevance
“…To overcome the limits of morphological assessment, recent studies have used a variety of molecular methods such as the nested polymerase chain reaction (PCR) 12 , real-time PCR 13 , pulsed field gel electrophoresis (PFGE) 14 , amplified fragment length polymorphism (AFLP) 15,16 , denaturing gradient gel electrophoresis (DGGE) 16 , random amplification of polymorphic DNA (RAPD) 16,17 , single strand conformation polymorphism (SSCP) 18 , terminal fragment length polymorphism (tFLP) 19 , restriction fragment length polymorphism (RFLP) [20][21][22][23] , and sequencing analysis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limits of morphological assessment, recent studies have used a variety of molecular methods such as the nested polymerase chain reaction (PCR) 12 , real-time PCR 13 , pulsed field gel electrophoresis (PFGE) 14 , amplified fragment length polymorphism (AFLP) 15,16 , denaturing gradient gel electrophoresis (DGGE) 16 , random amplification of polymorphic DNA (RAPD) 16,17 , single strand conformation polymorphism (SSCP) 18 , terminal fragment length polymorphism (tFLP) 19 , restriction fragment length polymorphism (RFLP) [20][21][22][23] , and sequencing analysis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The next-generation sequencing technology used in this study resulted in more than five million sequences, whereas approximately 140 isolates were recovered from the culturing method (Findley et al 2013). Sequence analysis revealed that Malassezia is the most abundant fungus on many human skin sites, as previously shown for the scalp (Gemmer et al 2002). These authors cultured three of the human-associated Malassezia species: M. globosa, M. restricta, and M. sympodialis.…”
Section: Human Microbiome Analysis Of Fungi From Skin and Other Body mentioning
confidence: 81%
“…The number of scalp Malassezia has been reported to be higher in patients with seborrheic dermatitis or dandruff than in normal controls (McGinley et al 1975), but the evidence is controversial and contradicted by other reports ). The differences are likely caused by the difficulty in accurately enumerating Malassezia from human skin (Kligman 1979;Weiss et al 1991;Gupta et al 2001b;Gemmer et al 2002;Sugita et al 2002). D/SD is most commonly treated by shampoos containing antifungal ingredients, indicating the role of fungi.…”
Section: Dandruff and Seborrheic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…In 1889, Baillon suggested that the genus of Malassezia was the cause pityriasis versicolor (5,6). In 1996 Gemmer et al based on 28S rRNA gene sequences classified Malassezia genus to seven species (7). Fourteen species of Malassezia genus have been identified based on phenotypic features and molecular methods (8 …”
Section: Introductionmentioning
confidence: 99%